The circular RNA circ0005654 interacts with specificity protein 1 via microRNA-363 sequestration to promote gastric cancer progression. Issue 1 (1st January 2021) - Yang, Cui; Han, Shengjin
ABSTRACT: Circular RNAs (circRNAs), a group of unique long noncoding RNAs, are involved in gastric carcinogenesis through multiple mechanisms, including interacting with microRNAs (miRNAs). Here, circ0005654, significantly upregulated in gastric cancer (GC), was chosen for further examination. circ0005654 was analyzed by RT-qPCR. The function of circ0005654 in GC cells was substantiated by loss-of-function assays. The mechanism of circ0005654 on miR-363/specificity protein 1 (sp1) axis was evaluated in GC cells by bioinformatics analysis, luciferase reporter, FISH, and ChIP assays. We observed that circ0005654 was enhanced in GC tissues and cells. Overexpression of circ0005654 was correlated with a poor long-term prognosis in patients with GC. Functionally, silencing of circ0005654 remarkably suppressed GC cell proliferation, migration and invasiveness in vitro and tumorigenesis and metastases in vivo . It was also established that circ0005654 served as a miR-363 sponge and enhanced sp1 expression. Furthermore, sp1 promoted GC carcinogenesis by regulating myc transcription to potentiate the Wnt/β-catenin pathway. In conclusion, circ0005654 expedites the GC development via miR-363/sp1/myc/Wnt/β-catenin axis and is a new biomarker for GC treatment regimen.